Kuwait : 2016 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2017)
This 2016 Article IV Consultation highlights that the economic activity in the non-oil sector in Kuwait has continued to expand, albeit at a slower pace, reflecting the impact of lower oil prices. Nonhydrocarbon growth slowed from 5 percent to an estimated 3.5 percent in 2015, as higher uncertainty weighed on consumption. Labor market reforms and efforts to promote the role of the private sector are important to foster diversification and boost job creation for nationals. Better aligning labor market incentives is necessary to encourage nationals to take on private sector jobs and private firms to create opportunities for them.